Pengaruh Minat dan Bakat Terhadap Kesuksesan Berwirausaha Mahasiswa Darullughah Waddawah (DALWA) Bangil Pasuruan - Indarti, Nunuk Indarti; Sugeng Pradikto (Universitas Negeri Semarang, 2024)
This study aims to determine the influence of interest and talent on the entrepreneurial success of DarullughahWadawah (DALWA) Pasuruan students class of 2018, with a total of 79 respondents .This research is a quantitative descriptive research, namely research by obtaining data in the form of numbers or quantitative data that is raised. The data was obtained from the 2018 Darullughah Wadawah Pasuruan student response questionnaire with quantitative analysis techniques using SPSS 25.The results of the study show that it can be known that the Fcal value is 6,508 with a significant value of 0.000, meaning that the significant value is smaller than the alpha level of 0.05. Thus it can be concluded that the research hypothesis is accepted. This means that there is a positive and significant influence between factors (interests and talents) on entrepreneurial success.